Georgia Architectural and Historic Properties Survey of 425 Mills St., Valdosta, Ga., December 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 425 Mills St., Valdosta, Ga., December 1980. One story house of rectangular plan. Gabled roof with exposed rafters. Gabled porch with square posts. Clapboard siding. Double hung sash windows with 2/2 lights. Set on brick piers. Fair condition. Date of Construction: App. 1900-1910. Typical vernacular house (functional). Significant as part of a potential N.R. district which covers 4 or 5 blocks.
Georgia Architectural and Historic Properties Survey of 425 Mills St., Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 81.3 MB (85,284,489 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)